Analysis of College Library Promotion Activities: Study on the Library Department of Governance Institute of Home Affairs (IPDN) - Rahmadanita, Annisa (Indonesian Journal of Librarianship, 2021)
Problem Statement: The author focuses on the obstacles faced in promoting IPDN libraries, which are limited budget, lack of human resource capabilities, and ratification of library promotion guidelines in 2021. Purpose: This study aims to obtaining a clear picture and analyzing promotional activities carried out by IPDN library. Method: The author collects data through interviews with first and second year students, and IPDN librarians. The author also conducted observations and documentation. Results: The results show that the form of promotion that is beneficial for users is through brochures, displays of new book collections and social media, especially Instagram. Meanwhile, promotion through the websiteneeds further development and improvement, especially in terms of updating information and utilizing the institution's website platform. Conclusion: There are several forms of promotion that have not been effectively carried out, one of which is promotion through the Library Website. Furthermore, there are still promotional methods that have not been carried out, including promotions in the form of making interactive CDs, creatinglibrarian blogs, competitions and book bazaars, and Praja internship programs in the library. Keywords: Promotion Activities; Promotion Forms; College Libraries.